First Annual Short Course in Educational Leadership : Littledale Conference Centre, St. John's, Newfoundland, February 22-27,1987. Day 3. Plenary session. Tape 2 of 3. - Memorial University of Newfoundland. School of Continuing Studies and Extension; Memorial University of Newfoundland. Division of Educational Technology (Memorial University of Newfoundland. School of Continuing Studies and Extension; Memorial University of Newfoundland. Division of Educational Technology, 1987)
Roger Grimes speaks about NTA's reaction to the report of the Royal Commission and some of the issues mentioned in the report. Dr. Boyce T. Fradsham, Assistant Deputy Minister Department of Education, speaks about schooling using the Royal Commission report as a focus and stresses the need for caution before making any changes. Dr. G.L. Parsons introduces the speakers.